Dynamics of differentiation of rural North-West of Russia: main trends and features - Alexander I. Kostyaev; Galina N. Nikonova (Baltic Region)
Excessive differentiation and polarisation in rural development lead to spatial compression, fragmentation, and social desertification, increasingly evident across many regions. This study aims to identify the trends, features and patterns of rural population differentiation in Russia’s North-West at interregional and intraregional levels. Methodologically, it adopted an approach that views rural space differentiation as a product of the combined influence of the agro-industrial complex system and the ‘urban-rural’ system. The changes of interest were studied from the industrial, demographic and settlement perspectives, with a focus on indicators such as changes in acreage and livestock between 1989, 2007 and 2023, and the size of the rural population and the number of residents per rural settlement between 2002, 2010 and 2020. The trends are investigated at the levels of regions — Leningrad, Novgorod and Pskov — and their municipalities. Hypotheses regarding the impact of the rental mechanism and core-periphery relations on the development differentiation of district territories were tested and largely confirmed. In the study regions, areas with varying rates of increase and decrease in acreage and livestock, including zones of compression and fragmentation, were identified, along with areas where the rural population grew or declined. Spatial differentiation in terms of resident per settlement ratio is shown to largely coincide with areas experiencing the most dynamic rural population change. The study concludes that, under the baseline scenario, the development of rural spaces in the Novgorod and Pskov regions will likely intensify their polarisation with the Leningrad region and lead to socio-demographic desertification of non-urbanised areas. The findings highlight the need for significant organisational and economic measures, engaging both public and private investments from outside these regions.